Designing of skull defect implants using C1 rational cubic Bezier and offset curves - Najihah, Mohamed; Ahmad, Abd Majid; Abd Rahni, Mt Piah; Zainul, Ahmad Rajion (AIP Publishing LLC., 2015)
Some of the reasons to construct skull implant are due to head trauma after an accident or an injury or an infection or because of tumor invasion or when autogenous bone is not suitable for replacement after a decompressive craniectomy (DC). The main objective of our study is to develop a simple method to redesign missing parts of the skull. The procedure begins with segmentation, data approximation, and estimation process of the outer wall by a C1 continuous curve. Its offset curve is used to generate the inner wall. A metaheuristic algorithm, called harmony search (HS) is a derivative-free real parameter optimization algorithm inspired from the musical improvisation process of searching for a perfect state of harmony. In this study, data approximation by a rational cubic Bézier function uses HS to optimize position of middle points and value of the weights. All the phases contribute significantly in making our proposed technique automated. Graphical examples of several postoperative skulls are displayed to show the effectiveness of our proposed method.